Analysis of surface integrity in drilling carbon fiber reinforced polymer composite material under various cooling/lubricating conditions - Nagaraj, Arjun; Uysal, Alper; Gururaja, Suhasini; Jawahir, I. S. (ELSEVIER SCI LTD, 2022)
Carbon Fiber Reinforced Polymer (CFRP) composite materials are a class of advanced materials widely used in versatile applications, including aerospace and automotive industries, due to their exceptional physical and mechanical properties. Owing to the heterogeneous nature of the composites, it is often a challenging task to machine them unlike metals. Drilling in particular, the most commonly used process for component assembly, is critical especially in the aerospace sector that demands parts of highest quality and surface integrity. Conventionally, all composites are machined under dry conditions. While there are drawbacks related to dry drilling, for example, poor surface roughness, there is a need to develop processes that yield good quality parts demonstrating improved surface integrity. This study aims at investigating the machining performance when drilling CFRP composite material under cryogenic (Cryo), minimum quantity lubrication (MQL) and hybrid (CryoMQL) conditions and comparing the performance with dry drilling in terms of the thrust force, torque, delamination, geometric error such as diametric variation, and surface integrity assessment including average surface roughness, hardness and sub-surface damage analysis. Additionally, the effects of varying the feed on the drilling performance were examined. Based on the results, it was concluded that drilling of CFRP composite material using coolant/lubricant outperformed dry drilling by producing better quality parts. Also, varying the feed proved to be advantageous over drilling at constant feed.
Keywords: CFRP composite; Hybrid (CryoMQL) drilling; MQL; Cryogenic cooling; Variable feed rate; Hole quality; Surface integrity; MECHANICAL-PROPERTIES; CUTTING FLUID; DELAMINATION; PERFORMANCE; PLASTICS; ROUGHNESS; TAGUCHI; WEAR; DRY; Engineering